2013
DOI: 10.1148/radiol.13122307
|View full text |Cite
|
Sign up to set email alerts
|

Unresectable Hepatocellular Carcinoma: MR Imaging after Intraarterial Therapy. Part I. Identification and Validation of Volumetric Functional Response Criteria

Abstract: Purpose:To identify and validate the optimal thresholds for volumetric functional MR imaging response criteria to predict overall survival after intraarterial treatment (IAT) in patients with unresectable hepatocellular carcinoma (HCC). Materials and Methods:Institutional review board approval and waiver of informed consent were obtained. A total of 143 patients who had undergone MR imaging before and 3-4 weeks after the first cycle of IAT were included. MR imaging analysis of one representative HCC index lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 39 publications
3
41
0
Order By: Relevance
“…The presented data by Chapiro et al [29] provided multilayer proof of the precision of 3D quantitative perfusion and diffusion-weighted MR imaging when correlated with pathologic examination as a standard of Ref. [14][15][16]. Our data demonstrated that volumetric analysis of functional MR imaging during the hepatic arterial and portal venous phase is superior because it There were several limitations to this study.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The presented data by Chapiro et al [29] provided multilayer proof of the precision of 3D quantitative perfusion and diffusion-weighted MR imaging when correlated with pathologic examination as a standard of Ref. [14][15][16]. Our data demonstrated that volumetric analysis of functional MR imaging during the hepatic arterial and portal venous phase is superior because it There were several limitations to this study.…”
Section: Discussionmentioning
confidence: 58%
“…On the contrary, anatomic metrics did not show any significant change in the responders or non-responders after therapy. Our results suggest that these potential novel functional MRI techniques can stratify patients as responders and non-responders early (1 month) after TARE, even before changes in tumor size and/or morphologic characteristics occur [16,25].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Importantly, volumetric techniques were shown to have a strong influence on how tumor response is classified and in some studies, the classification of patients as responders or nonresponders was shown to differ between 3D and non-3D techniques in up to one-third of the analyzed cases (12,13). Furthermore, 3D quantitative techniques have been repeatedly shown as beneficial in identifying tumor response more accurately, primarily because they include the whole tumor tissue into the analysis (14,15) . For assessment of radiological response after TACE, 3D volumetric measurement has a strong clinical impact to be able to accurately measure what part of the lesion is necrotic and viable(16).…”
Section: Discussionmentioning
confidence: 99%
“…By imaging, partial response to therapy was defined from baseline as a ‡30% reduction for the maximal diameter in the transverse plane according to the RECIST criteria; as a ‡30% reduction for the maximal diameter of tumor enhancing portions in the transverse plane according to mRECIST criteria and as a reduction ‡65% of the tumor volume (volumetric transformation of RECIST criteria) [1,2,16]. Complete response was defined as the absence of visible tumor (for RECIST and Volume criteria) or the absence of enhancing tumor portions (for mRECIST).…”
Section: Imaging and Pathological Response Assessmentmentioning
confidence: 99%